Clinical safety of ibuprofen in pediatric practice - T.P. Borysova (Zaslavsky O.Yu., 2021)
The article presents a review of the literature on the side effects of ibuprofen in children. The international guidelines recommend ibuprofen as an antipyretic and analgesic drug in pediatrics. The drug is characterized by a high profile of efficacy and safety in the treatment of children with fever, mild to moderate pain. Ibuprofen in over-the-counter doses has a low probability of serious side effects from the gastrointestinal tract and kidneys. Side effects of ibuprofen are transient and resolve after discontinuation of treatment. Circumstances associated with a higher risk of adverse events are highlighted. The use of ibuprofen is contraindicated in children with dehydration, which is associated with a risk of acute kidney damage. Caution should be exercised when prescribing ibuprofen to children with community-acquired pneumonia due to the risk of purulent complications. Ibuprofen should not be prescribed to patients with chickenpox to avoid bacterial superinfections. Ibuprofen should be used with caution in children with diseases of the gastrointestinal tract, liver, renal failure, hemorrhagic syndrome, anticoagulant therapy. Ibuprofen is allowed in children with bronchial asthma unless a personal or family history of aspirin-induced asthma. Caution should be exercised when treating premature infants or low birth weight infants due to the reduction in nephron mass and, therefore, the increased risk of renal damage. Ibuprofen should not be used in patients who are sensitive to this drug or other non-steroidal anti-inflammatory drugs. Ibuprofen should be taken in the minimum effective dose and discontinued as soon as possible - no more than 3 days for fever and 5 days for pain.